Persepsi Siswa Terhadap Pembelajaran Penjas Materi Bola Basket Berbasis Daring pada Siswa Kelas VIII SMP Negeri 21 Kota Bekasi di Masa Pandemi - Dewi Astuti; Akhmad Dimyati; Muhammad Mury Syafei; Dhika Bayu Mahardhika (Peneliti.net, 2021)
The purpose of this study was to find out how much understanding and knowledge of class VIII students at SMP Negeri 21 Bekasi City in learning physical education material based online basketball during the pandemic period. The data collection technique used in this study was the survey method, with the data collection technique using a questionnaire to class VIII students. This research questionnaire has a reliability of .702 cronbach's alpha. The population in this study was class VIII students at SMP Negeri 21 Bekasi City with a sample of 86 students consisting of two classes that the researchers chose randomly. The instrument used is in the form of a Guttman scale questionnaire using Google forms. The data analysis technique used descriptive quantitative statistical analysis and percentages using SPSS version 24. The level of knowledge obtained from class VIII students about basketball learning at SMP Negeri 21 Bekasi City was 57 students with a percentage of 66.3% having a good level of knowledge about basketball and as much as 29 students with a percentage of 33.7% in the sufficient category